INCIDENCE OF RIFAMPICIN-RESISTANCE PRESUMPTIVE M. TUBERCULOSIS CASES AMONG OUTPATIENTS IN KEBBI STATE, NIGERIA - Danlami, Mohammed Bashar; Aliyu, Basiru; Samuel, Grace (African Journal of Infectious Diseases (AJID), 2020)
Background: The present study determined the incidence of rifampicin resistance M. tuberculosis among outpatients at the General Hospital Yauri, Kebbi State, Nigeria. Materials and Methods: The study is a cross-sectional study conducted from February 2018 to October 2019. Sociodemographic data were collected from hospital registration books. Rifampicin resistance M. tuberculosis was detected using GeneXpert Model GX-IV following manufacturers’ instruction. Descriptive statistics and logistic regression were computed using SPSS version 20. The results were presented as odds ratios with associated 95% confidence intervals, and P-value at 0.05. Result: Of the 837 samples, 65.8% (551/837) were males, and 34.2% (286/837) females, 11.4% (95/837) HIV-seropositive. M. tuberculosis was detected in 15.5% (130/837), of which 116/130 (89.23%) were males and 14/130 (10.77%) females. M. tuberculosis-HIV coinfection was detected in 9.47% (9/95) of HIV positive. Rifampicin resistance was observed in 1.3% (11/837), 7.7% (10/130) in M. tuberculosis patients and 1.05% (1/94) in HIV seropositive. In logistic regression, the odds ratio for having a rifampicin-resistant M. tuberculosis was 0.49 (0.15-1.54) for > 30 years; taking <30 years as the reference value, 1.02 (1.00-1.03) for male; taking female as the reference value, and 0.78 (0.09-6.15) for HIV positive, taking negative as the reference value. Conclusion: This study reported the current incidence rate of rifampicin-resistant M. tuberculosis at the General Hospital Yelwa Yauri, Kebbi State, Nigeria, among presumptive TB patients. Patients diagnosed with rifampicin-resistant M. tuberculosis were predominantly male adults. Thus, frequent screening is vital for surveillance and reduces the risk of transmission and spread of M. tuberculosis